Computational Thinking Skill of Prospective Mathematics Teachers in Statistic Methods Courses - Ansori, Hidayah; Juhairiah, Juhairiah; Amalia, Rizki (Tarbiyah : Jurnal Ilmiah Kependidikan, 2025)
The statistics methods course is compulsory in the Mathematics Study Program, which uses applications according to technological developments, including the SPSS application. This study describes the computational Thinking of prospective mathematics teachers in solving statistics problems in statistics methods courses. This research is quantitative-qualitative descriptive research. The subjects were 88 students in the statistics methods course in the 2022/2023 academic year. The research instrument was a test containing three statistics problems. The findings have indicated that the computational Thinking of prospective mathematics teachers in solving statistics problems was in the Very Good Category with a percentage of 2,27%, the Good Category was 31,8%, the Enough category was 38,64%, the low Category was 19,32%, and the deficient Category was 7,95%. The researchers suggest that ongoing research needs to be conducted to improve students' computational thinking skills, and it is necessary to look for factors that influence students' computational thinking skills.